Herpes simplex induced necrotizing tonsillitis in an immunocompromised patient with ulcerative colitis - Jansen, Laura (World J Clin Cases, 2016)
We here present the case of a 22-year-old female of Suriname ethnicity with ulcerative colitis who received treatment with mercaptopurine and infliximab. She presented herself with a severe necrotizing tonsillitis due to herpes simplex virus type-1 (HSV-1). Combination therapy consisting of immunomodulators and anti-tumor necrosis factor (TNF) agents is increasingly being used. Anti-TNF therapy is associated with an increased risk of developing serious infections, and especially patients receiving combination treatment with thiopurines are at an increased risk. We here show that HSV infections can cause a severe tonsillitis in immunocompromised patients. Early recognition is essential when there is no improvement with initial antibiotic therapy within the first 24 to 72 h. HSV infections should be in the differential diagnosis of immunocompromised patients presenting with a necrotizing tonsillitis and can be confirmed by polymerase chain reaction. Early treatment with antiviral agents should be considered especially if antibiotic treatment fails in such patients.